Răspuns :
Explicație:
2koh+h2so4=>2H2O+k2so4
m(koh)=200*0,056=11.2g
v(koh)=11.2/56=0.2mol
v(H2O)=0.2mol
v(h2so4)=0.2/2=0.1mol
v(k2so4)=0.1mol
m(H2O)=0.2*18=3.6g
m(k2so4)=0.1*174=17.4g
m(h2so4)=0.1*98=9.8g
m.sol(h2so4)=9.8*100/49=20g
este posibil să fi făcut greșeli la calcul dar metoda e corectă
M KOH=39+16+1=56 g/mol
M H2SO4=2*1+32+16*4=98 g/mol
M K2SO4=39*2+32+16*4=174 g/mol
M H2O=2+16=18 g/mol
C KOH=100md/ms=>md=C*ms/100=5,6*200/100=5,6*2=11,2 g KO
11,2 g x z y
2KOH + H2SO4--->K2SO4 + 2H2O
2*56 98 174 2*18
11,2/(2*56)=x/98=>x=(11,2*98)/(2*56)=(11,2*98)/112=9,8 g H2SO4
11,2/(2*56)=y/(2*18)=>y=(11,2*2*18)/(2*56)=(11,2*18)/56=3,6 g H2O
11,2/(2*56)=z/174=>z=(11,2*174)/(2*56)=(11,2*174)/112=17,4 g K2SO4
Dar, C H2SO4=49%, CH2SO4=100md/ms<=>100md=C*ms=>ms=100md/C=(100*9,8)/49=20 g soluție H2SO4